European climate policy and aviation emissions - Karen Mayor; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
We use a model of international and domestic tourist numbers and flows to investigate the effect of various climate policy instruments implemented in Europe on arrivals and emissions for the countries concerned. We find that these schemes do not fulfil their desired effects. The introduction of aviation into the European Trading system results in a fall in the number of tourists travelling into the EU in favour of other destinations. It also causes a significant welfare loss with only a small reduction in emissions. The flight taxes in the Netherlands and the United Kingdom result in different substitution effects across destinations (depending on the zones being taxed) but both policies do have the same consequence of inducing welfare losses and also reducing visitor numbers to the countries. We find that when these policies are combined their effects are additive. Welfare impacts are robust to variations in the underlying assumptions and changes in the scope of the taxes examined have the expected effects.
Keywords: 330; climate policy; carbon dioxide emissions; international tourism; EU-Umweltpolitik; Tourismus; Luftverkehr; Umweltbelastung; Kohlendioxid; Ökosteuer; Wohlfahrtseffekt; EU-Staaten